Antiplatelet therapy in patients with Covid-19: A retrospective observational study - Banik, Jozef; Mezera, Vojtech; Köhler, Christian; Schmidtmann, Marco (Thrombosis update, 2021)
INTRODUCTION: Covid-19 is associated with a high risk of venous thromboembolism. In addition, cases of arterial thromboembolism were also reported. We investigated the effect of antiplatelet therapy on the disease course. METHODS: We evaluated a cohort of inpatients with Covid-19 (n ​= ​152). We recorded the patient's demographic data, their comorbidities, medication use including the use of antiplatelets and anticoagulants, laboratory findings and data about mechanical ventilation. We then separated the patient's outcomes into either being "bad" (dead or referral to higher level of care) or "good" (discharged). Then we evaluated the factors that contributed to the patient needing ventilatory support and to showing typical radiological findings. RESULTS: In our cohort, 21 patients received ventilatory support whereas 131 did not require the use of ventilators. 127 patients had good outcomes and 25 had bad outcomes. By using multivariate analysis, we found that the need for ventilatory support was the strongest predictor of a bad outcome. All patients who were on ventilators displayed typical radiological findings. The factors predicting the need for ventilatory support were LDH and CRP levels, the presence of cardiac conduction abnormalities as well as chronic lung conditions. Cardiac conduction abnormalities, LDH and CRP levels, and the use of antiplatelets, were factors that predicted typical radiological findings. CONCLUSIONS: There was a higher incidence of typical radiological findings in patients on antiplatelet medication. However, it did not translate into changes in the ventilation requirement or in the outcome. The need for mechanical ventilation was the strongest predictor of a bad outcome.
Keywords: Aspirin; Covid-19; Antiplatelet agents; Anticoagulants; Acetylsalicylic acid